Women Farmers’ Groups as a Learning Resource in the Community Economy Course to Develop Young Generation’s Character Strengths in the Agricultural Sector - Kiromim Baroroh; Ngadiyono Ngadiyono; Ratna Rosita Pangestika (Program Studi Pendidikan Ekonomi FKIP Universitas Lambung Mangkurat, 2026)
Sustainable development requires preparing the younger generation to engage in agriculture as a backbone of the national economy. This study examines the utilization of Women Farmers’ Groups (Kelompok Wanita Tani, KWT) as a contextual learning resource in the Community Economy course at the Faculty of Economics and Business, Universitas Negeri Yogyakarta. The research objectives are: (1) to identify the use of KWT as a learning resource, (2) to classify the obstacles faced in its utilization, and (3) to analyze students’ character strengths in agriculture. A descriptive quantitative method was employed with 178 students as respondents. Data collection techniques included questionnaires, observations, interviews, and documentation. The research instrument was validated (83 valid items out of 84, Cronbach’s Alpha = 0.978). Results indicate that KWT significantly improves students’ understanding of agrarian-based Community economy, with increased interest in agribusiness and sustainability awareness. The main obstacles encountered were technical limitations (data access) and psychological barriers (lack of confidence). Student participation in KWT strengthened their character strengths, particularly courage, teamwork, gratitude, and empathy. The findings highlight the relevance of integrating community-based resources in higher education to bridge theory and practice while empowering local agricultural communities.